A Rare Case of Primary Anorectal Melanoma and a Review of the Current Landscape of Therapy - Ho-Man Yeung; Brinda Gupta; Bhishak Kamat (Greater Baltimore Medical Center, 2020)
Introduction: Anorectal mucosal melanoma (ARMM) is an uncommon and highly aggressive malignancy. Given its rarity, there is insufficient evidence on the optimal medical management which presents as a clinical challenge to its diagnosis and treatment. Treatment of ARMM typically involves a multimodal approach including surgical resection, chemotherapy, targeted therapy and/or immunotherapy. Case Presentation: Here, we present a case of a 78-year-old female who presented with a four-month history of rectal bleeding and bowel incontinence. Ultimately, colonoscopy revealed a mass at the anal verge, and biopsy of the mass showed malignant cells that stained positive for S100, Melan-A and HMB-45, consistent with the diagnosis of malignant melanoma. Molecular testing revealed no BRAF, KIT or NRAS gene mutations. PD-L1 immunohistochemistry showed tumor proportion score of 1%. She underwent abdominoperineal resection with a plan to initiate immunotherapy with an anti-PD-1 checkpoint inhibitor. This case highlights a rare aggressive malignancy and reviews its treatment option, which are mostly extrapolated from its cutaneous counterpart and some derived from a few case reports. Due to its rarity, there is no consensus guideline for the treatment of ARMM.